PENGARUH HIGH PERFORMANCE WORK ENVIRONMENT TERHADAP EMPLOYEE ENGAGEMENT FEELING & BEHAVIOR GENERASI MILENIAL - Alvina Putri Prasetyanto; Novianty Kresna Darmasetiawan (Jurusan Ilmu Ekonomi Prodi Ekonomi Pembangunan Fakultas Bisnis dan Ekonomika Universitas Surabaya, 2022)
Human Resources as the driving force of a company is one of the most important assets that need to consider. Therefore, it is of utmost importance to have employee engagement to minimize the turnover rate in the company. A supportive and conducive work environment is one factor in the formation of employee engagement. This research was conducted to see the effect of a high-performance work environment on employee engagement feelings and employee engagement behavior among millennials. This is due to the abysmal engagement rate of millennial employees, which can affect the companies turnover rate. The respondents of this study are millennials aged 22-38 years and have a minimum working period of 2 years in state-owned and private companies. This study uses a quantitative approach that uses the SEM method for data processing. The results are that a high-performance work environment has a significant positive effect on employee engagement with a critical ratio value of 4.651. Employee engagement feeling has also significantly positively affected employee engagement behavior with a critical ratio of 5.727. Based on the results of this research, the company can implement a work environment that facilitates the needs of the millennials so that it can reduce the turnover rate